Analysis of the distribution of titanium oxide nanoparticles on paintings. Issue 1 (1st April 2022) - Pasquale, S.; Politi, G.; Pronti, L.; Romani, M.; Viviani, G.; Cestelli Guidi, M.; Angelucci, M.; Gueli, A.M.
Abstract: This work is addressed to analyse the distribution of titanium dioxide nanoparticles on painting crossing data coming from two methodologies. Scanning Electron Microscope and Proton Induced X-Ray emission techniques have been employed in the study of the interaction between a colloidal dispersion constituted by titanium dioxide nanoparticles and the painting surface. The former e was used to understand and morphology of the painting and to investigate the distribution of the nanoparticles on the entire cross section of the pictorial layers. Proton induced X-ray emission is aimed at examining the surface titanium distribution by mapping. This study is important because the exploitation of the photocatalytic activity of the titanium dioxide is possible only in the case of absorption of proper energy that can promote the oxide reduction reactions and thus the dirt and dust degradation.